Analyzing multidisciplinary uses and impact of innovative technologies - Marchisio, Emiliano (IGI Global, 2022)
Technology faces rapid advancements every year, and each year, its uses in various facets of society increase and become more profound. Every discipline has adopted technology in some capacity. From FinTech in the business realm to phygital churches in the realm of religion, innovation is applicable everywhere. It is essential that professionals study how to use these advancements to their advantage and also to examine their impact on society and its multitude of sectors.